Immunoprotection by recombinant ABA392 vaccines against Pasteurella multocida mediated haemorrhagic septicaemia / Kang Tzin Lim - Kang , Tzin Lim (2019)
Haemorrhagic septicaemia (HS) is a well-known high fatality septicaemia disease among bovines. The disease is caused by the Pasteurella multocida serotype B:2 bacteria. P. multocida B:2 has high mortality and morbidity rates and is spread through the intranasal and oral routes in bovines. The aim of the study was to investigate the efficacy of the recombinant protein vaccine, ABA392/pET-30a and DNA vaccine, ABA392/pVAX1 against the P. multocida B:2 infection via intranasal inoculation by targeting the mucosal immunity. The constructed recombinant protein and DNA vaccine were subjected to an animal study using Sprague Dawley rats as our animal model. The study was divided into two major parts which were active and passive immunization studies and involving 108 animals in total, 54 animals each of which was divided into 4n groups (n=6) and 5n groups (n=6) for protein and DNA vaccine respectively. Both active and passive immunization studies involved the determination of immunogenicity and histopathogenicity. The results demonstrated that total white blood cell and immunoglobulins IgA and IgG increased after each three dosage of vaccination administration. The IgA and IgG development of both tested groups: group 1 (50μg/ml protein & DNA vaccine) and group 2 (100μg/ml protein & DNA vaccine) showed equivalent with the positive control group 4 (formalin-killed P. multocida B:2) for protein vaccine and group 5 (formalin-killed P. multocida B:2) for DNA vaccine. However, there was a significant difference when compared with the negative control group 3 (normal saline) for both protein and DNA vaccine and with the negative control group 4 (pVAX1 vector alone) for DNA vaccine. From the studies, higher concentration of protein vaccine at 100μg/ml showed higher development of both IgA and IgG compared to 50μg/ml protein vaccine. However the result was totally opposite for DNA vaccine whereas lower concentration of DNA vaccine at 50μg/ml showed higher development of both IgA and IgG compared to 100μg/ml DNA vaccine. Higher and rapid development of IgA compared to IgG showed that mucosal immunity has been induced through the intranasal administration of both the protein vaccine and DNA vaccine. In addition, leucocytosis and neutrophilia was observed at each dose of vaccination showed that both the protein and DNA vaccine are capable to induce the immune responses of the host. In summary, both test sample groups showed significant difference (p < 0.05) compared to the negative control groups whereas no significant differences (p > 0.05) was observed between the test samples groups against positive control. These results demonstrated that both the protein and DNA vaccine has the same efficacy as the commercially available positive control vaccine. Furthermore, histopathogenicity studies of the vaccinated groups showed more bronchus associated lymphoid tissue (BALT) formation and no severe lesions after bacterial infection challenge compared to the negative control group. Besides, no inflammatory responses were observed after the intranasal inoculation. In conclusion, both recombinant protein vaccine ABA392/pET-30a and DNA vaccine ABA392/pVAX1 could be a potential prophylaxis through intranasal administration which can provoke mucosal immunity against HS disease.